Carbon‐Based Metal‐Free Catalysts for Energy Storage and Environmental Remediation. Issue 13 (28th January 2019) - Hu, Chuangang; Lin, Yi; Connell, John W.; Cheng, Hui‐Ming; Gogotsi, Yury; Titirici, Maria‐Magdalena; Dai, Liming
Abstract: Owing to their high earth‐abundance, eco‐friendliness, high electrical conductivity, large surface area, structure tunability at the atomic/morphological levels, and excellent stability in harsh conditions, carbon‐based metal‐free materials have become promising advanced electrode materials for high‐performance pseudocapacitors and metal–air batteries. Furthermore, carbon‐based nanomaterials with well‐defined structures can function as green catalysts because of their efficiency in advanced oxidation processes to remove organics in air or from water, which reduces the cost for air/water purification and avoids cross‐contamination by eliminating the release of heavy metals/metal ions. Here, the research and development of carbon‐based catalysts in supercapacitors and batteries for clean energy storage as well as in air/water treatments for environmental remediation are reviewed. The related mechanistic understanding and design principles of carbon‐based metal‐free catalysts are illustrated, along with the challenges and perspectives in this emerging field. Abstract : The research and development of carbon‐based metal‐free catalysts in pseudocapacitors and batteries for clean energy storage, as well as in air/water treatments for environment remediation are reviewed. The related mechanistic understanding and design principles of carbon‐based catalysts are illustrated, along with the challenges and perspectives in this emerging field.